Reciprocal On-Site Access: Sharing Information by Sharing Library Spaces. Issue 1 (2nd January 2020) - Posner, Beth; DeVito, Jennifer; Haldeman, Katharine; Massie, Dennis
Abstract: On-site reciprocal access to libraries is a valuable benefit of consortial membership. This article details its advantages, offers a sample of some ways in which consortia facilitate such access and reviews the work of the authors, within the SHARES consortium, in this area. Relevant challenges to creating policies, as well as suggestions about how to determine best practices, will also be offered for librarians and their partners to consider and build upon.